II. MEASURES: SECURE BASE BEHAVIOR, CO‐CONSTRUCTION, AND ATTACHMENT SCRIPTS. Issue 4 (5th December 2018) - Posada, Germán E.; Waters, Harriet S.
ABSTRACT: In order to examine the interplay between behavioral and cognitive representations of attachment during early childhood, we compiled both behavior‐based and more cognitive‐based attachment measures for this age range. The behavior‐based measures were observational Q‐set methodologies already established in the literature. Measures of attachment representations for the children and mothers were narrative‐based procedures, that is, established storytelling tasks for obtaining attachment narratives from children and adults. For assessing maternal co‐construction processes, we developed two new co‐construction tasks that required joint storytelling of attachment relevant storylines in one case, and joint conversations about emotion‐laden situations in the other. All of these measures are based on the central secure base construct of attachment theory. Behavioral measures assess secure base use and support. Attachment narratives collected from both children and parents are scored for secure base script knowledge. Maternal co‐construction is assessed in terms of cognitive processes that enhance and promote attachment script knowledge.